Individual and Communal Character Building, Woman, Responsibilities: Gender Study in Light of Prophetic Biography - Bilal Hussain; Dr.Abdul Rahman; Dr. Abbas Ali; Dr. Kulsoom Fatima; Dr. Imtiaz Ahmad; Dr.Muhammad Irfan (Al-Qanṭara, 2022)
ABSTRACT Rights and responsibilities are two sides of one coin. The modern world's familiarity with human rights and women's rights is high. Women are more responsible individuals than men in the building of society rather than a deprived or subordinated identity. The contemporary Muslim world is suffering from a crisis of women's social and civic roles. Unfortunately, due to misreading or misinterpretation, or lack of Islamic teachings, a woman’s separate identity has been diminished in present Muslim society. Islam provided a variety of portfolios for women to develop character in both individual and communal life in society, such as wife, mother, daughter, sister, teacher, and so on. The Prophetic era acknowledged women’s independent identity and gave them a key role in reforming society. In the 20th century, feminist movements were started and present vibes are more threatening to Muslim societies. Muslim women need to recognise their role and respond to western feminist vibes. This study will explore women’s social and civic roles to build the character of an individual as well as a society. It will bring out prophetic practise indicating women’s independent identity and their key role in society. The status of women in the modernization of society will be the main topic of the essay at hand. It will open up new opportunities for academics to share their knowledge and help advance the status of women in the development of future generations' moral character. This study will not only dispel myths about women's gender and social standing in the Muslim world but also promote women's participation in societal norms.